2016
DOI: 10.1128/mcb.01085-15
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Regulation of TIP60 and Poly(ADP-Ribose) Polymerase 1 in Damaged-Chromatin Dynamics

Abstract: fThe dynamic exchange of histones alleviates the nucleosome barrier and simultaneously facilitates various aspects of cellular DNA metabolism, such as DNA repair and transcription. In response to DNA damage, the acetylation of Lys5 in the histone variant H2AX, catalyzed by TIP60, plays a key role in promoting histone exchange; however, the detailed molecular mechanism still is unclear. Here, we show that the TIP60 complex includes poly(ADP-ribose) polymerase 1 (PARP-1). PARP-1 is required for the rapid exchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…Out of these, two DNA repair genes previously unconnected to PARPi resistance, namely the histone acetyltransferase KAT5 (also known as TIP60) and E3 ubiquitin ligase HUWE1, drew our attention. Both proteins have roles in cellular processes related to DNA replication and repair and are potential interactors of PARP1 21 , 22 , yet they have not been directly connected to PARPi sensitivity. We first sought to validate these two hits.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these, two DNA repair genes previously unconnected to PARPi resistance, namely the histone acetyltransferase KAT5 (also known as TIP60) and E3 ubiquitin ligase HUWE1, drew our attention. Both proteins have roles in cellular processes related to DNA replication and repair and are potential interactors of PARP1 21 , 22 , yet they have not been directly connected to PARPi sensitivity. We first sought to validate these two hits.…”
Section: Resultsmentioning
confidence: 99%
“…Less studied modifications of H2A.X are acetylation, methylation and SUMOylation, some of which also contribute to DDR by recruiting repair factors. Acetylation of K5 by TIP60 does not only facilitate ubiquitination at K119 and mobility [ 76 , 77 ], it is also required for the accumulation of the repair factor NBS1 and Poly-ADP-ribosyl-polymerase 1 (PARP1/ARTD1) activity [ 132 , 133 ]. Methylation of K134 is involved in the repair process and contributes to the recruitment of the kinases ATM and ATR [ 79 ], but the function of Suv39H2 as K134 methylase is highly controversial [ 80 ].…”
Section: Features and Post-translational Modifications Of H2az Hmentioning
confidence: 99%
“…An additional line of inquiry has examined the contribution of PARP1 in the exchange rate (incorporation or eviction) of histone variants. A recent study reported that a reciprocal cooperation between the acetylation of H2AX at lysine 5 (K5Ac) catalysed by the acetyltransferase TIP60 complex and PARP1 activation is required to facilitate histone H2AX exchange at damage sites [28]. The acetylation of H2AX-K5 by TIP60 is needed for the dynamic binding of PARP1 to damaged chromatin and the subsequent local synthesis of PAR.…”
Section: Parp1-catalysed Par Configures Chromatin Shape At Sites Of Dmentioning
confidence: 99%